Ecological health assessment of the Qinghe River Basin: analysis and recommendations - Jingcheng Lei; Jinfeng Zhang; Peiying Li; Hongliang Zhang; Chengbin Xu (Journal of Water and Climate Change, 2024)
The assessment of ecosystem health at the scale of a large river basin is currently an important direction in environmental science and landscape ecology research. This study focuses on the ecological health assessment of the Qinghe River Basin. Following the Guidelines for Eco-health Assessment of Basin (Trial), a framework was designed to construct an assessment system. The aquatic and terrestrial systems of the Basin were selected, and the ecological pattern, ecological function, and ecological pressure were evaluated. The comprehensive assessment index, i.e., whole health index (WHI), was used to evaluate the overall situation of the basin, providing a comprehensive reflection of its state. The results indicate that the comprehensive index of ecological health assessment for the Qinghe River Basin is 58.66, indicating an average evaluation grade. By evaluating the health of the ecological system in the Qinghe River Basin, this study has gained an understanding of the current situation and identified major issues in the area. The study also proposes suggestions for future sustainable development and effective management of the Qinghe River Basin. These findings hold significant practical importance for the comprehensive protection and development of the area. HIGHLIGHTS Adopting a comprehensive assessment framework, including aquatic and terrestrial ecosystems, using the whole health index for comprehensive assessment.; The evaluation covers the entire Qinghe River Basin, providing a comprehensive understanding and evaluation.; Provided theoretical and practical guidance for sustainable development.; The evaluation results provide decision-making basis for policymakers.;